Quad-Copter for Security Surveillance - T M Thamizh Thentral, A Geetha, S Usha, Tanya Sengupta, Ishan Kar, Kritika Raj (International Journal of Advanced Science and Technology, 2020)
The security system and all its    appraisals in the modern era play a vital role in many different fields of interest such as home, industries and high networking systems. The use of security systems is varied by interest particularly in electronics, automation and mass information systems. The role played by security systems is innate and can be viewed as an area of development for young Research enthusiasts. One of the major evolving fields of security systems are the aerial support systems which, so far, have been implemented on the Military background and are yet to be souvenired to the domestic background. The use of the most efficient technology is Quadcopters and drones that allow for enhanced security surveillance. Quad-copters are a primary development in the aforementioned topic. The paper focuses on all the necessary calculations, components required sidewise verified by a model prototyped. The paper also discusses the various needs for a Quadcopter to have a steady security system use.